2013
DOI: 10.2478/s13386-013-0143-4
|View full text |Cite
|
Sign up to set email alerts
|

Multi-method luminescence investigations on quartz grains of different sizes extracted from a loess section in Southeast Romania interbedding the Campanian Ignimbrite ash layer

Abstract: Abstract:In this study we present luminescence investigations of four samples of loess bracketing the Campanian Ignimbrite/Y5 tephra at the Rasova-Valea cu Pietre site, on the eastern bank of the Danube River, southeastern Romania. Investigations involved SAR-OSL dating on aliquots of fine (4-11 μm) and medium-grained (63-90 μm) quartz, as well as single grain analyses on 125-180 μm quartz. Luminescence dating results coupled with glass-shard chemical fingerprinting assign the depositional age and origin of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 89 publications
0
18
0
Order By: Relevance
“…The good agreement of the ages obtained using different grain sizes of quartz in the low dose range increases our confidence in the accuracy of the SAR-OSL ages for samples with equivalent doses of about 100 Gy or less, as further confirmed by comparison with independent age control provided through tephrochronology (Constantin et al, 2012;Anechitei-Deacu et al, 2014) or radiocarbon dating (Trandafir et al, 2015). On the other hand, the age discrepancy of SAR-OSL ages previously reported for Romanian and Serbian loess for ages beyond~40 ka (equivalent doses >~100 Gy) was also found to be characteristic of Chinese loess.…”
Section: Resultsmentioning
confidence: 70%
“…The good agreement of the ages obtained using different grain sizes of quartz in the low dose range increases our confidence in the accuracy of the SAR-OSL ages for samples with equivalent doses of about 100 Gy or less, as further confirmed by comparison with independent age control provided through tephrochronology (Constantin et al, 2012;Anechitei-Deacu et al, 2014) or radiocarbon dating (Trandafir et al, 2015). On the other hand, the age discrepancy of SAR-OSL ages previously reported for Romanian and Serbian loess for ages beyond~40 ka (equivalent doses >~100 Gy) was also found to be characteristic of Chinese loess.…”
Section: Resultsmentioning
confidence: 70%
“…2012; Timar-Gabor et al, 2011, 2012Timar-Gabor and Wintle, 2013); it has been suggested that this may reflect variations in depositional processes and source sediment of the different size fractions (Anechitei-Deacu et al, 2014) but at present the cause of these discrepancies is unclear. At present, the most reliable quartz OSL dating results for Danubian loess appear to derive from finegrained material, for ages up to ca.…”
mentioning
confidence: 99%
“…At present, the most reliable quartz OSL dating results for Danubian loess appear to derive from finegrained material, for ages up to ca. 70 ka , and loess sections in Romania have been successfully dated within these limitations (Anechitei-Deacu et al, 2014;Constantin et al, 2012Fitzsimmons et al, 2013Fitzsimmons and Hambach, 2014), alongside sections in Serbia (Schmidt et al, 2010, Stevens et al, 2011. However, studies employing quartz OSL in Hungary have sometimes met with poor quartz luminescence properties such as low signals and reproducibility, although reliable ages may be obtained (Schatz et al, 2012).…”
mentioning
confidence: 99%
See 2 more Smart Citations